Enhanced cycling performance of Si-MXene nanohybrids as anode for high performance lithium ion batteries - Zhu, Xiaoquan; Shen, Jiale; Chen, Xifan; Li, Yang; Peng, Wenchao; Zhang, Guoliang; Zhang, Fengbao; Fan, Xiaobin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
•The sandwiched structure of Si/Ti3C2 hybrid release the strain of Si particles.•The Ti3C2 layers can effectively alleviate volume variation of Si anode.•The Si/Ti3C2 hybrid shows improved cycling performance than pristine Si. The practical application of Si anodes is hampered by huge volume expansion during lithiation/delithiation process, leading to poor cycling performance and electrode fracture. To overcome such weakness, a sandwich-like Si/d-Ti3C2 hybrids are fabricated and show an excellent reversible capacity of 1130 mA h g−1 at a current density of 500 mA g−1 after 200 cycles. Comparing with pristine Si, the improved electrochemical performance of Si/d-Ti3C2 hybrids can be attributed to the fact that the d-Ti3C2 MXene can significantly enhance the electronic conductivity of electrode and support integrity of electrodes. The Si/d-Ti3C2 hybrids perform their promising prospect in lithium ion batteries.